Women in security forces - a bibliometric study / Mujeres en las fuerzas de Seguridad: un estudio bibliométrico - Oliveira Bagalho, Jaqueline (Red de Investigación en Salud en el Trabajo; Vol. 2 Núm. Especial 2 (2019): Memorias del 6to Foro de Investigación en Salud en el Trabajo - Memorias del 1er. Congreso PREVENCIONAR (Diciembre), 2020)
Women in the police force, in this review, represented by the Portuguese police (responsible for public safety), the Federal Police of Brazil (responsible for border and road safety) and the specialized US police (FBI - intelligence services ) have common characteristics to the studies of women in the armed forces. Some studies indicates that family-work conflicts are more evident for police women, who opt for an administrative career to reconcile work and career. However, not without burden, then, career advancement in operational activities is faster and has more opportunities. This investigation demonstrates that, when both are police (couple) it is up to the woman to abdicate the career progression to reconcile with the children and housework.